No rebound effect after a course of clopidogrel in patients with acute TIA or minor stroke. (2nd November 2022) - Zhang, Xinmiao; Jing, Jing; Zhao, Xingquan; Liu, Liping; Wang, Anxin; Pan, Yuesong; Wang, David; Johnston, S. Claiborne; Wang, Yilong; Wang, Yongjun; Meng, Xia
ABSTRACT: Background and Purpose: Previous studies demonstrated that discontinuation of clopidogrel in patients after ACS was associated with a rebound increase in risk of recurrent events. In this study, we aimed to investigate the rebound effect after discontinuation of clopidogrel therapy in patients with TIA or stroke. Methods: All patients with minor stroke or TIA were recruited from the Clopidogrel in High-Risk Patients With Acute Nondisabling Cerebrovascular Events (CHANCE) trial. Patients were divided into two groups: patients who discontinued clopidogrel and switched to aspirin therapy   (Clopidogrel Discontinuation Group) and patients who continued one mono-antiplatelet therapy (non-Clopidogrel Discontinuation Group) during 90-180  days. The outcomes included risks of recurrent ischemic stroke, recurrent TIA, and composite events during 90-180  days. The prevalence of each outcome was compared between two groups for every 30 days. Further subgroup analysis was conducted in patients with and without CYP2C19 loss-of-function alleles. Results: Among the 3456 patients included, a total of 10 patients in the Clopidogrel Discontinuation Group and 11 patients in the non-Clopidogrel Discontinuation Group presented ischemic stroke recurrence during the 90–180-day period. The inter-group comparisons were not significant in each 30 days. Similar results were found for recurrent stroke, recurrent TIA, and composite events in these two groups, which were also found in CYP2C19 subgroup analysis. Conclusions: No rebound increase in the risk of ischemic stroke and composite events was found during the 90 days after discontinuation of clopidogrel therapy in patients with TIA or minor stroke in the CHANCE trial. Trial Registration: clinicaltrials.gov Identifier: NCT00979589